2018
DOI: 10.1021/acs.energyfuels.8b02439
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Surface Structure of Coal Caused by Igneous Intrusions and Their Effect on the Wettability

Abstract: In this paper, normal and thermally altered coals were sampled to investigate the surface characteristic changes of coals after igneous intrusions and their effects on the wettability. The chemical compositions, pore structures, surface morphology, and functional groups of coals after igneous intrusions were comparatively analyzed. A contact angle experiment and wetting time test were employed to analyze the wettability of coals. The results showed that the coals after igneous intrusions exhibited much more ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In this work, the contact angle was measured with distilled water; the volume of one water drop was about 2 μL, and the test procedure was the same as in the previous study. 19 The infrared spectrum analysis was conducted, and the testing range is 4000−400 cm −1 with a resolution of 4 cm −1 according to the Chinese National Standard GB/T 6040-2019. The test method of low-temperature N 2 physisorption is the same as in the previous study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, the contact angle was measured with distilled water; the volume of one water drop was about 2 μL, and the test procedure was the same as in the previous study. 19 The infrared spectrum analysis was conducted, and the testing range is 4000−400 cm −1 with a resolution of 4 cm −1 according to the Chinese National Standard GB/T 6040-2019. The test method of low-temperature N 2 physisorption is the same as in the previous study.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, various studies have been undertaken to investigate the relationship between wettability and coal surface roughness. Li 20 and Zhou 21 reported that the rougher the solid surface, the poorer the wettability, and some scholars gave a contrary finding, 19,22 while other scholars found that a certain degree of surface roughness is best for coal wetting. 23 In conclusion, the mineral content, chemical structure and element composition, pore structure, surface morphology, and particle size of coal dust are the factors affecting coal wettability, while the coal-forming environment such as tectonic stress and magma intrusion has an important influence on those factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Semenova 37 studied the chemical structure of coal with different metamorphic degrees and concluded that the higher the content of hydroxyl and carboxyl, the better the coal wettability. Shi et al 38 indicated that the pore structure, ash, and minerals are the main factors to improve the wettability of magmatic intrusive coal. In summary, all of the concentrations and structures of surfactants and the physicochemical properties of coal are influencing factors of the coal wettability.…”
Section: Introductionmentioning
confidence: 99%